2022
DOI: 10.3390/ijerph19031116
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Thyroid Cancer Risk: An Update

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy worldwide and its incidence has increased dramatically in recent years. In parallel, the prevalence of overweight and obesity has also increased, suggesting a possible link between these two diseases. Indeed, low-grade chronic inflammation, altered cytokine levels, insulin resistance, oxidative stress, and hormonal changes that occur in obese patients are all factors that contribute to the occurrence and growth of TC. In this review, the most recent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 142 publications
0
51
1
2
Order By: Relevance
“…In summary, we speculate that sex hormones may be related to the occurrence of thyroid disease. A number of studies have confirmed that obesity is a risk factor for thyroid diseases, such as hypothyroidism and thyroid cancer [27][28][29]. However, our results seemed to be slightly different from previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In summary, we speculate that sex hormones may be related to the occurrence of thyroid disease. A number of studies have confirmed that obesity is a risk factor for thyroid diseases, such as hypothyroidism and thyroid cancer [27][28][29]. However, our results seemed to be slightly different from previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies have confirmed that obesity is a risk factor for thyroid diseases, such as hypothyroidism and thyroid cancer [ 27 29 ]. However, our results seemed to be slightly different from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is a common endocrine malignancy ( 1 , 2 ). Although THCA has a low mortality rate and a relatively good prognosis, the existing therapeutic modalities for locally advanced or recurrent metastatic THCA are still ineffective in improving the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Останнім часом ожирінню (ОЖ) приділяється багато уваги щодо наявності зв'язків між ОЖ та розвитком пухлин. Ожиріння пов'язане з хронічним запаленням, що характеризується неспецифічною активацією імунної системи, збільшенням чинників запалення та виробленням цитокінів і адипокінів, прямо або опосередковано визначає проліферацію клітин та спричиняє пухлиноутворення в різних тканинах, зокрема в ЩЗ [38]. Метааналіз [109] виявив статистичне значуще збільшення ризику РЩЗ в осіб із надлишковою масою тіла на 25 % порівняно з однолітками з нормальною масою тіла, в осіб з ОЖ -на 55 %.…”
Section: ожирінняunclassified